Emotional Tone and Sound Symbolism in Poetry: A Phonosemantic Experimental Study (Eurasian Journal of Philology Science and Education, 2026)
This article examines the relationship between emotional tone and sound symbolism in Kazakh poetry based on experimental data. The study is grounded in phonosemantic theory, which considers speech sounds not only as formal units but also as cognitive carriers of emotional and evaluative meaning. The experiment was conducted using Charles Osgood’s semantic differential method. A total of 100 participants from three age groups took part in an online survey administered via Google Forms. They evaluated 12 poetic texts using three bipolar scales. The collected data were processed in Jamovi using descriptive statistics and associative comparisons. The results revealed a systematic relationship between vowel quality and emotional evaluation. Specifically, texts dominated by back vowels were perceived as more “powerful,” “heavy,” “dark,” and “harsh,” whereas texts with a higher frequency of front vowels were associated with being “bright,” “light,” “soft,” and “weak.” These patterns were consistent across all age groups, indicating the universal nature of sound symbolism. The findings confirm that the emotional tone of poetic texts is shaped not only by semantic content but also by phonetic structure. This study contributes to phonosemantic, cognitive, and psycholinguistic approaches to poetic discourse and opens new perspectives for experimental analysis of poetic language.Keywords: sound symbolism, phonosemantics, emotional tone, poetry, semantic differential.